Plastic pollution on Durance riverbank: First quantification and possible environmental measures to reduce it - Ballerini, Tosca; Chaudon, Nathalie; Fournier, Marc; Coulomb, Jean-Paul; Dumontet, Bruno; Matuszak, Eléonore; Poncet, Justine (Frontiers in Sustainability, 2022)
Plastic pollution is one of the most pressing issues of our time, with negative impacts on natural ecosystems, human health, and the climate system. The identification of top litter items discarded in the environment is essential to prioritize environmental policies to prevent plastic leakage and promote a circular economy. Here, we present the first quantification on macrolitter on three sites along Durance riverbank and one site on Lake Serre-Ponçon’s beach, in the Région SUD - Provence-Alpes-Côte d’Azur, southeastern France. Data were collected through Citizen Science between 2019 and 2020 in 3 sampling occasions (autumn, winter, spring) on Durance riverbank and in 22 occasions on Lake Serre-Ponçon. A total of 25’423 litter items were categorized, of which 82% were plastics. Single-use plastic items correspond to 8.13% of total, while single-use plastic bottles are among the top 10 litter items at each site. Median litter abundance across all samples is 2081 items / 100 m survey, two orders of magnitude higher than European precautionary threshold value for marine litter (20 items/100 m survey). The majority of items (74.83%) were small and non-identifiable. Pieces of polystyrene, soft plastics and rigid plastics represented the majority of litter items in total (56.63%) and at S1 (89.28%), S2 (58.95%) and S3 (79.60%). Glass pieces corresponded to 15.83% of total litter items. Soft plastic pieces are the most abundant litter category overall and correspond to 58.85% of litter items at sampling site along Durance riverbank located in an agricultural zone, suggesting their source from agricultural plastic mulch films. Among the identifiable items, the most abundant were plastic biomedia used in waste water treatment plants and single-use beverage bottles in plastic and in glass. The development of extended producer responsibility schemes for plastic mulch films and plastic biomedia and of deposit return schemes for single-use beverage bottles is suggested as a way to prevent leakage in the environment. This work confirms the opportunity to use citizen science to gather relevant data on macro litter items and to monitor the effectiveness of environmental regulations to reduce plastic pollution.